Chora-graphy and Performative Arts: interweaving and co-existing of space and body in the turn of the 21st century - Volanakis, Adonis (My University, 2020)
The subject of this doctoral thesis is the multiple meeting spaces of practices from the performing and visual arts as it is manifested at the beginning of the 21st century, in the western world, and their description by the term "chora-graphy". In this term coexist the two key concepts of the present thesis: the space (through the first constituent, "chora-"), and the in-scription of the bodies of the artists and/or of the spectators. In the introduction we unravel the threads that constitute the theoretical and research framework, so that the reader comprehends the approach mechanism and the operating methodology adopted for the space-body-viewer triangle. For the analysis of chora-graphy, we connect it with Performance Studies and its broader phenomena in art as well as with spatial theories. Since chora-graphy can be defined as a practice of interweaving –performing arts (theater, opera, contemporary dance), and visual arts (performance, installation, social sculpture) function vertically as threads, as a warp while horizontally, almost as a weft, they are associated with concepts and practices such as the ritual as a maternal origin, ancient tragedy, the meeting of bodies, opening a space that leads to hospitality, walking practice, dialogue, experience of time, manifestations of Greekness, co-learning, the alternation of the attributes and roles of artists and spectators– in the main body of the dissertation we study works as nodes. In regards to the performing arts we focus at: a text-based theater where the performers act without directorial instructions (J. Kokkos); the transforming sculptural installation for a series of various opera performances (St. Lazaridis); in contemporary dance, works in transitional spaces of a museum (M. Hassabi), and the practice of walking in an archeological site (T. Sehgal). As to the visual arts, we study two performance works: in the first, the body in pain is exposed parallel to the bodies of the viewers in a museum (Franco B); in the second, the artist moving in the urban fabric, recalls and produces spatial memories (L. Papakonstantinou). Later on, regarding the visual installation, we focus the research (J. Kounellis) on a project / meeting place between living species (human-animal). Finally, we analyze a social sculpture / creation center (Victoria Square Project) that is materialized by, with and for communities. The "dance" of chora-graphy, from one practice to another and vice versa, captures after all another type of “tribe” of artists, which is characterized by a desire to meet the viewer/ visitor and open spaces for common, ephemeral co-habitation. In continuation of the present research, we propose a chora-graphical framework of education / teaching in Greece.
Keywords: Mise-en-espace; Chora-graphy; Performative arts; Visual arts; Body; Space; Spectator; Time; Ritual; Expanded scenography; Performance; Installation art; Theatre; Opera; Contemporary dance; Ancient tragedy; Collaboration; Social sculpture; Phenomenology; Community based art; Hospitality; Walking practice